Effectiveness of Constitutional Homoeopathic Medicines in Cases of Urticaria (Advancements in Homeopathic Research, 2023)
Urticaria is localized dermal oedema, characterized  by marked itchy wheals which may be pale or red in  the centre and surrounded by a red flare.
Keywords: Urticaria; Urticaria activity score 7; Homoeopathy